High-frequency variations of hydrogen spectral lines in the B3V star η UMa - Pokhvala, S.M. (Advances in Astronomy and Space Physics, 2015)
We reported the detection of high-frequency variations in the hydrogen Balmer lines in the hot star η UMa of spectral class B3V. Spectral observations of η UMa were carried out with slitless spectrograph (R ∼ 100) installed on the 60 cm Carl Zeiss telescope in the Andrushivka Observatory. Spectra were obtained with a time resolution in the sub-second range. It has been found that the η UMa shows rapid variations in the hydrogen lines Hα, Hβ, Hγ, as well as variations in the atmospheric oxygen lines. The intensity variations in the hydrogen lines varies from 0.2% to 0.5% , and that of the oxygen lines is approximately 2%.